Delay in diagnosis of lung cancer: a case report - Ching, Siew Mooi; Chia, Yook Chin; Cheong, Ai Theng (Universiti Putra Malaysia Press, 2014)
This case report highlights delay in the diagnosis of adenoma carcinoma of the lung in a female patient who has never smoked. It took three months to reach the diagnosis of stage IV lung carcinoma despite the presence of symptoms and an abnormal chest radiograph finding from the beginning. The clinical characteristics and predictors of missed opportunities for an early diagnosis of lung cancer are discussed. In this case, patient and doctor factors contributed to the delay in diagnosis. Thus, early suspicions of lung cancer in a woman with the presence of respiratory symptoms despite being a non-smoker are important in primary care setting.